Ultrasound-guided percutaneous venting duodenostomy: New technique - Khamaysi, Iyad; Leiderman, Maxim; Hajj, Eisa; Yassin, Kamel (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Khamaysi I, Leiderman M, Hajj E, Yassin K. Ultrasound-guided percutaneous venting duodenostomy: New technique. Turk J Gastroenterol 2020; 31(12): 962-3.